RETRACTED: A CRITICAL ANALYSIS OF ISLAMIC ECONOMIC OPPORTUNITIES AND CHALLENGES IN GLOBALIZATIONAL ERA - Ahmad Maulidizen; Mohammad Taqiuddin Mohammad (Share: Jurnal Ekonomi dan Keuangan Islam, 2018)
This manuscript HAS BEEN RETRACTED on request of the author due to development of a reported case (plagiarism). Therefore, a reasonable effort should be made to remove all references that links to this article.